Periodontitis sebagai Faktor Penyebab Kelahiran dengan Berat Badan Lahir Rendah - Dewi Sodja Laela; Dewi Purwaningsih; Asep Iwan Purnawan (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2009)
Low weight birth infant has been persistently become a public health problem, which is one of causes of death, and in a long term period could be a risk factor of nerve disorder and other health problems. Periodontal disease could take a role in etiological factors in pathogenesis of premature born of low weight birth infants. Sitokin and other inflammatory mediators that are produced by periodontitis could damage the local tissue and could reach a level that influences the cardiovascular system and the placenta tissue.. The research aim is to investigate the role of periodontitis as a cause of low weight birth infant. The research use analytical case control design, while the sampling method was purvosive sampling. The hypothesis testing is applied by using the Odds Ratio and Multivariate Logistic Regression. The research result is expected to be used as a reference for preventive program of premature born of low weight birth infants. In this respect the periodontal tissue should be taken into account as other infection diseases, which could influence maternal and infant health. The analysis of logistic regression from 8 variables that influence the occurrence of BBLR has found that only 2 variables significantly influence the occurrence of BBLR, which are periodontitis and anemia as the confounding variable. The value of Odds Ratio (OR) is 77, which explains that a pregnant woman who is suffering from periodontitis risks 77 times to give a birth of low weight birth infant compared to non-periodontitis pregnant woman.